Palynomorphs from the Gorstian (Silurian) of the Sazes Formation (Buçaco Syncline), Central Iberian Zone, Portugal - preliminary results - Lopes, Gilda (2014)
Occuring in a complex syncline that extends from Buçaco to Penedo de Góis, the studied area is located in the Central Iberian Zone of the Iberian Massif. In this region outcrops a well-preserved and complete stratigraphic succession of Lower Paleozoic age. At the top of the Buçaco Syncline stratigraphic succession, the Silurian Sazes Formation (Paris, 1981), is currently being studied at a palynological (miospores and chitinozoans) and macrofossil (graptolites) level, allowing a preliminary revision and completion of the initial biostratigraphy of this area. This studies will also provide information to support the undergoing surveying mapping project (1:50 000) that is being undertaken by the “Laboratório Nacional de Energia e Geologia” (Portuguese Geological Survey) (Sequeira, in prep).